2009
DOI: 10.1111/igc.0b013e3181a3e1bf
|View full text |Cite
|
Sign up to set email alerts
|

Parity and Time Interval Since Childbirth Influence Survival in Endometrial Cancer Patients

Abstract: Parity and time interval since last birth have been found to be associated with the risk of endometrial cancer, but few previous studies have examined whether these reproductive factors have prognostic impact. We examined this issue among 740 nulliparous and 3355 parous endometrial cancer patients diagnosed in Norway during the period 1961-1999. The mean age at diagnosis was 55.7 years (range, 25-74 years). Hazard ratios (HRs) with 95% confidence intervals were calculated in Cox proportional regression models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
4
7
0
Order By: Relevance
“…Age at diagnosis, age at menarche, parity, menopausal age, menstrual status, hormonal contraception, and hormone replacement therapy are well known risk factors for developing the cancer [2, 3, 11, 13, 17, 18], but as in our study, their role as prognostic factors predicting survival remains controversial. Only higher number of pregnancies was correlated with better DFS, and our results match well with those of Alkbretsen et al [19] reporting the relationship between obstetric history and prognosis in endometrioid endometrial cancer patients. They found better survival in parous than nulliparous women, and in the study the improved effect was strongest for women with the shortest time interval since the last childbirth.…”
Section: Discussionsupporting
confidence: 92%
“…Age at diagnosis, age at menarche, parity, menopausal age, menstrual status, hormonal contraception, and hormone replacement therapy are well known risk factors for developing the cancer [2, 3, 11, 13, 17, 18], but as in our study, their role as prognostic factors predicting survival remains controversial. Only higher number of pregnancies was correlated with better DFS, and our results match well with those of Alkbretsen et al [19] reporting the relationship between obstetric history and prognosis in endometrioid endometrial cancer patients. They found better survival in parous than nulliparous women, and in the study the improved effect was strongest for women with the shortest time interval since the last childbirth.…”
Section: Discussionsupporting
confidence: 92%
“…In analyses adjusted for age at diagnosis, clinical stage, and histological type, the HR for parous versus nulliparous women was 0.68 (95% confidence interval, 0.57-0.82) (Albrektsen, et al, 2009) and also reports were similar in an earlier study (Bratos et al, 2002). Similar observations were found in the present study where nulliparous women had poor prognosis than parous women.…”
Section: Discussionsupporting
confidence: 78%
“…1 It has been noted that these tumors have clinical characteristics more similar to high-grade endometrial carcinomas, 1,2,4,5 but differences also exist. 6Y8 Similar to findings for patients with endometrial carcinoma, 9,10 nulliparity was found in 1 study to adversely affect prognosis in patients diagnosed with CS. 11 Two other studies, 12,13 however, could not confirm this finding.…”
supporting
confidence: 60%
“…1,11 In relation to our finding of a beneficial prognostic impact of parity in endometrial cancer patients, 10 we hypothesized that pregnancy progesterone may have had a favorable effect in the very early and undetected phase of disease. In view of their finding among CS patients, Marth et al 11 hypothesized that a pregnancy-induced alteration in protein content in uteri, or immunologic mechanisms, could lead to improved resistance to dissemination.…”
Section: Discussionmentioning
confidence: 99%